Study Of The Prevalence Of Hypertension In Children And Adolescents In Lisbon And Tejo Valley Region - Simão, Carla (2025)
Introduction: Hypertension (HTN) is an important risk factor for cardiovascular disease (CVD) at any age. Its prevalence in children is estimated at 3-5%. The knowledge of its prevalence allows for the adequacy of control, treatment and prevention measures, to decrease the morbidity and mortality associated with CVD. Objectives: To assess the prevalence of hypertension in school-age children and adolescents and the effect of sociodemographic and clinical variables on the blood pressure profile. To compare the values using the classification criteria of the blood pressure defined by the European Society of Hypertension (ESH-2016) with the American Academy of Pediatrics criteria (AAP-2017). Methodology: Multicenter, observational, prospective, cross-sectional study conducted between 2016 and 2019. The convenience sample is composed of children aged between 6-18 years, living in Lisbon and Tejo Valley Region. Blood pressure (BP) measurement by oscillometric method was performed in school environment. The classification of the BP profile into normal BP (NBP), elevated BP (EBP) and hypertension (HTN) was based in ESH-2016 criteria. Age, gender, race, education level, weight and height were recorded. A descriptive statistical analysis was performed. Results: Participants: 1245 children, 215 from 6-10 years (17%); 720 from 11-15 years (58%) and 310 from 16-18 years (25%). Caucasian:88%; Female gender: 635 (51%). There were 16% overweight and 7% obese. The prevalence of HTN is 8.4% and EBP is 12.8%. Between 6-10 years old: 5.6% had HTN; 11-15 years old: 8.6% and 16-18 years old: 10%. In boys, 10.5% had HTN (vs F.6.5%-p<0.001). Caucasians: 8.7% with HTN, 6% in blacks and 5.9% among Asians. Children who were overweight or obese showed higher values of hypertension, 17% and 26% respectively. Discussion/Conclusion: The prevalence of hypertension is high (8.4%) and it increases with age, male gender and more advanced level of education. Overweight and obesity contribute to the increase of HTN cases.